Site, dance and body movement, materials and corporeal engagement - Hunter, Victoria (Senior lecturer in dance) (Palgrave Macmillan, 2021)
How does the moving, dancing body engage with the materials, textures, atmospheres, and affects of the sites through which we move and in which we live, work and play? How might embodied movement practice explore some of these relations and bring us closer to the complexities of sites and lived environments? This book brings together perspectives from site dance, phenomenology, and new materialism to explore and develop how site-based body practice can be employed to explore synergies between material bodies and material sites. Employing practice-as-research strategies, scores, tasks and exercises the book presents a number of suggestions for engaging with sites through the moving body and offers critical reflection on the potential enmeshments and entanglements that emerge as a result. The theoretical discussions and practical explorations presented will appeal to researchers, movement practitioners, artists, academics and individuals interested in exploring their lived environments through the moving body and the entangled human-nonhuman relations that emerge as a result.